1990
DOI: 10.1111/j.1745-4603.1990.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

TEXTURE AND MICROSTRUCTURE OF AFRICAN YAM BEAN (SPHENOSTYLIS STERNOCARPA) PRODUCTS

Abstract: The microstructure of African yam bean (Sphenostylis sternocarpa) cotyledons, flour, starch and gel prepared from flour were examined using scanning electron microscopy. Smooth starch granules varying in size and shape were embedded in the protein matrix. The starch granules maintained their integrity in the flour after milling. The texture profile parameters of starch and flour gels were studied at both 50 and 75% double compression and relaxation levels using the Instron Universal Tester. Significant variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
5
3
Order By: Relevance
“…The seeds of AYB differ in texture across germplasm; they could be rough, wrinkled, or smooth. The electron microstructure study of seeds revealed the presence of smooth starch granules exhibiting different sizes and shapes [57]. The cells were bounded by cell walls same as observed in other legumes [58,59].…”
Section: Structure Of African Yam Bean Seedssupporting
confidence: 55%
“…The seeds of AYB differ in texture across germplasm; they could be rough, wrinkled, or smooth. The electron microstructure study of seeds revealed the presence of smooth starch granules exhibiting different sizes and shapes [57]. The cells were bounded by cell walls same as observed in other legumes [58,59].…”
Section: Structure Of African Yam Bean Seedssupporting
confidence: 55%
“…The modified method of Lii & Chang (1981) described by Enwere et al (1990) was used for starch extraction from the seeds.…”
Section: Starch Extractionmentioning
confidence: 99%
“…However, the characteristic hard-to-cook syndrome and lack of commercial exploitation is creating a waning interest in its cultivation. Thus studies aiming at providing alternative methods of utilizing African yam bean have been a novel idea (Eke & Akobundu, 1993;Enwere, Hung, & Ngoddy, 1990;Ofuya, Njoku, & Eli, 1991).…”
Section: Introductionmentioning
confidence: 99%